2019
DOI: 10.5194/acp-19-5853-2019
|View full text |Cite
|
Sign up to set email alerts
|

Near-surface and path-averaged mixing ratios of NO<sub>2</sub> derived from car DOAS zenith-sky and tower DOAS off-axis measurements in Vienna: a case study

Abstract: Abstract. Nitrogen dioxide (NO2), produced as a result of fossil fuel combustion, biomass burning, lightning, and soil emissions, is a key urban and rural tropospheric pollutant. In this case study, ground-based remote sensing has been coupled with the in situ network in Vienna, Austria, to investigate NO2 distributions in the planetary boundary layer. Near-surface and path-averaged NO2 mixing ratios within the metropolitan area of Vienna are estimated from car DOAS (differential optical absorption spectroscop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…Several studies have discussed in detail the impact of algorithmic differences on the NO 2 column uncertainty, which can reach 42 %, mainly due to tropospheric AMF uncertainties (Lorente et al, 2017). The underestimation of the NO 2 satellite products identified here at a large number of stations confirms what was obtained in previous validation exercises using fewer sites and different satellite products (Celarier et al, 2008;Brinksma et al, 2008;Vlemmix et al, 2010;Irie et al, 2008aIrie et al, , 2012Lin et al, 2014;Halla et al, 2011;Shaiganfar et al, 2011;Ma et al, 2013;Kanaya et al, 2014;Wang et al, 2017b;Mendolia et al, 2013;Tzortziou et al, 2014;Lamsal et al, 2014;Drosoglou et al, 2017;Herman et al, 2019;Judd et al, 2019;Compernolle et al, 2020). These studies generally reported small negative or positive biases over rural (unpolluted) measurement sites and stronger (systematic) negative biases over urban polluted sites.…”
Section: Impact Of the Satellite Pixel Selectionsupporting
confidence: 85%
“…Several studies have discussed in detail the impact of algorithmic differences on the NO 2 column uncertainty, which can reach 42 %, mainly due to tropospheric AMF uncertainties (Lorente et al, 2017). The underestimation of the NO 2 satellite products identified here at a large number of stations confirms what was obtained in previous validation exercises using fewer sites and different satellite products (Celarier et al, 2008;Brinksma et al, 2008;Vlemmix et al, 2010;Irie et al, 2008aIrie et al, , 2012Lin et al, 2014;Halla et al, 2011;Shaiganfar et al, 2011;Ma et al, 2013;Kanaya et al, 2014;Wang et al, 2017b;Mendolia et al, 2013;Tzortziou et al, 2014;Lamsal et al, 2014;Drosoglou et al, 2017;Herman et al, 2019;Judd et al, 2019;Compernolle et al, 2020). These studies generally reported small negative or positive biases over rural (unpolluted) measurement sites and stronger (systematic) negative biases over urban polluted sites.…”
Section: Impact Of the Satellite Pixel Selectionsupporting
confidence: 85%
“…The in-situ telemetric air quality network (Bruxelles Environne ment/Leefmilieu Brussel) of the Brussels region is used for verifying the retrieved near-surface NO2 VMR. Previous studies (e.g., Kramer et al, 2008;Schreier et al, 2019a)) have compared NO2 MAX-DOAS measurements with in-situ concentrations, concluding to a considerable underestimation of NO2…”
Section: Comparison Of Max-doas and In-situ Measure Mentsmentioning
confidence: 99%
“…Car-DOAS observations have been used for quantification of total emissions from urban or industrial emission sources [25,26], comparisons with satellite observations [27][28][29], validation of airborne DOAS measurements [30,31] and for comparisons with model simulations [29,32]. Also, car-DOAS measurements have recently been used for comparison with in situ measurements [33].…”
Section: Introductionmentioning
confidence: 99%